Krzysztof Ożóg, The Role of Poland in the Intellectual Development of Europe in the Middle Ages [Krakow Historical Monographs, vol. I], Societas Vistulana, Kraków 2009, ss. 231. - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2012)
Krzysztof Ożóg, The Role of Poland in the Intellectual Development of Europe in the Middle Ages [Krakow Historical Monographs, vol. I], Societas Vistulana, Kraków 2009, ss. 231.